Experience of orofacial injuries and use of mouthguards - a survey in German elite sport - Merle, C. L.; Rott, T. A.; Rauch, A.; Wolfarth, B.; Wüstenfeld, J.; Haak, R.; Schmalz, G.; Ziebolz, D. (Clinical Journal of Sport Medicine, 2026)
Objective: This study aimed to assess the experience of orofacial injuries and sports mouthguard use in German elite athletes.